2010
DOI: 10.1016/j.jcrimjus.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A tale of three cities: Crime and displacement after Hurricane Katrina

Abstract: a b s t r a c t a r t i c l e i n f oWhen Hurricane Katrina struck New Orleans in August 2005, it greatly disrupted both the physical and social structures of that community. One consequence of the hurricane was the displacement of large numbers of New Orleans residents to other cities, including Houston, San Antonio, and Phoenix. There has been media speculation that such a grand-scale population displacement led to increased crime in communities that were recipient of large numbers of displaced New Orleans r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 22 publications
5
43
0
1
Order By: Relevance
“…Thus, some exceptions can occasionally be observed after disasters. However, it still seems reasonable, on the whole, to assume that the crime rate of the disaster-affected areas did not generally increase in post-disaster years in Japan, consistent with what disaster researchers in Western countries have been claiming over the past decades [3,9,16,45].…”
supporting
confidence: 63%
“…Thus, some exceptions can occasionally be observed after disasters. However, it still seems reasonable, on the whole, to assume that the crime rate of the disaster-affected areas did not generally increase in post-disaster years in Japan, consistent with what disaster researchers in Western countries have been claiming over the past decades [3,9,16,45].…”
supporting
confidence: 63%
“…Smaller increases are also seen for robbery, forcible rape, and murder. All these increases have been found in the literature (including Hussey, Nikolsko-Rzhevskyy, and Pacurar 2011;LeBeau 2002;Leitner and Helbich 2011;Thornton and Voigt 2007;Varano et al 2010). For example, Thornton and Voigt (2007) reported that women became rape victims in the wake of hurricane Katrina.…”
Section: Discussion Of Resultsmentioning
confidence: 83%
“…The state experienced temporary increases in domestic violence and burglary (LeBeau 2002). Phoenix, Arizona saw significant increases in murder after the passing of hurricane Katrina due population displacement in New Orleans (Varano et al 2010). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Outmigration of the working aged household members may result in disrupted family ties, socioeconomic instability, and thus increasing risk of becoming victim of a crime in the place of origin. Empirical evidence on the relationship between migration and crime is mixed (Moehling and Piehl 2009, Stowell and Martinez 2007, Varano et al 2010). Stowell and Martinez (2007) argue that any effort to predict the relationship between migration and crime must consider the context in which migration occurs.…”
Section: Rural Areas In Transformation and Migrationmentioning
confidence: 99%